Komposil: Empowering Jarak Village Youth Through Coffee Husk Waste Innovation For Sustainable Eco-Agri - Ikhlashotul Amaliyyah; Linggar Hanggar Biantoro; Muhammad Aldi Almi; Siti Fatimah; Dian Anik Cahyani (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Jarak Village in Wonosalam, Jombang, faces critical environmental challenges due to hundreds of tons of accumulated coffee husk waste (cascara) that degrade local sanitation. Conversely, local coffee farmers remain highly dependent on expensive synthetic chemical fertilizers, which accelerate soil degradation. This community service program aimed to enhance the technical capacity of the local youth organization (Karang Taruna) by transforming agricultural biomass into an eco-friendly compressed fertilizer called KOMPOSIL. The service method applied the Participatory Learning and Action (PLA) approach, focusing on intensive training, hands-on mechanical practices, and reflective discussions. The program actively engaged 16 youth members over a four-month period at the village hall. The results showed a significant improvement in the partners' motoric and technical skills, with 85% of participants successfully mastering the operation of the Integrated Homogenizer machine and manual hydraulic press tools independently. The production of this slow-release cylinder block fertilizer effectively mitigates open-dumping pollution while providing a sustainable organic input alternative for community plantations, establishing a resilient foundation for community-based ecological independence.